Diálogos velados: a negociação dos papéis femininos em Jane Eyre (1847) e A Intrusa (1908) - Caetano, Bruna dos Santos (Universidade Federal de São Carlos, 2025)
This thesis has two novels as objects of analysis: Jane Eyre (1847), by the english writer Charlotte Brontë (1816-1855), and A Intrusa (1908), by the brazilian writer Júlia Lopes de Almeida (1862-1934). Although she lived part of the Victorian Age, a period when the “Angel in the House” ideology was consolidated, Brontë introduced new feminine patterns, such as Jane Eyre, protagonist of the namesake novel, who stands out for seeking independence in a patriarchal society. Similarly, Júlia Lopes de Almeida lived in a society that propagated the Rainha do Lar ideal, reinforced by the roles of mother, wife and housewife. Nevertheless, Almeida centralized Alice Galba in A Intrusa, who seeks independence and living through work. Even though the novels are from different nationalities, the characters are similar as they move between the ideal role of “Angel in the House”, reaffirming the patriarchal culture, and, at the same time, subvert this pattern, seeking independence and living through work. Therefore, considering the historical-social context of the english and brazilian societies, this research aims to make a comparative study between the protagonists of Jane Eyre and A Intrusa, pursuing to identify, comprehend and compare the negotiations of the feminine roles in the novels. Through the character analysis, we aim to identify veiled dialogues, veiled criticisms, of the system that limited feminine roles. For that, the study is based on the dialectical criticism by Fredric Jameson (1992), and intends to comprehend, from a reading in three levels, the connection between the works and the historical-social field they are inserted and, posteriorly, how this exterior field is figured in the narratives. Furthermore, we also have the feminist criticism as a reading perspective, because we offer a new interpretation for the novels.
Veiled criticism: the negotiations of feminine roles in Jane Eyre (1847) and A Intrusa (1908)
Keywords: Jane Eyre; A Intrusa; Negociação de papéis; Crítica velada; Autoria feminina; Negotiations of roles; Veiled criticism; Female Authorship; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA COMPARADA